Idea sprawiedliwości społecznej w kontekście procesu globalizacji - Kowalczyk, ks. Stanisław (Annales. Etyka w Życiu Gospodarczym, 2008)
The subject of social justice are groups or whole societies – also states, object of this justice aretheir mutual rights and common good. The process of economic and technological globalization meansamong other things: establishment of the world market, predominant role of international companies,centralization of leading elites’ decisions, financial disproportion between individual peopleand countries. In the teaching of contemporary popes (John XXIII’s, Paul VI’s, John Paul II’s) the ideaof social justice has also international dimension and therefore process of economic globalization oughtto respect two principles of the Church’s social teaching: the principle of the subsidiarityand the principle of solidarity. The principle of the subsidiarity demands to respect subjectivity of allnations and states as well as to aid their integral development. The principle of solidarity postulatescreation of common good of world society, this good are: peace, economic prosperity, commerceprofitable for all states, cooperation and financial help of rich countries for underdeveloped countries.The social justice in the international dimension is the expression and the imperative of solidarity of allnations and states.